Brain anatomy of the marine isopod Saduria entomon Linnaeus, 1758 (Valvifera, Isopoda) with special emphasis on the olfactory pathway - Matthes eKenning; Steffen eHarzsch (Frontiers Media S.A., 2013)
Representatives of at least six crustacean taxa managed to establish a terrestrial life style during their evolutionary history and the Oniscidea (Isopoda) are currently held as the most successfully terrestrialized malacostracan crustaceans. The brain architecture of terrestrial isopods is fairly well understood and studies on this field suggest that the evolutionary transition from sea to land in isopods coincided with a considerable size reduction and functional loss of their first pair of antennae and associated brain areas. This finding suggest that terrestrial isopods may have no or poor abilities to detect volatile substances but that their chemosensory ecology is most likely restricted to contact chemoreception. In this study, we explored how the brain of a marine isopod and particularly its olfactory system compares to that of terrestrial relatives. Using histochemical and immunohistochemical labeling, brightfield and confocal laser-scan microscopy, we show that in the marine isopod Saduria entomon aesthetascs on the first pair of antennae provide input to a well defined deutocerebrum. The deutocerebral chemosensory lobes are divided into spherical neuropil compartments, the olfactory glomeruli. Secondary processing areas in the lateral protocerebrum are supplied by a thin but distinct projection neuron tract with a contralateral connection. Hence, contrary to terrestrial Isopoda, S. entomon has at least the neuronal substrate to perceive and process olfactory stimuli suggesting the originally marine isopod lineage had olfactory abilities comparable to that of other malacostracan crustaceans.